2009
DOI: 10.1016/j.neuron.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Training Improves Multitasking Performance by Increasing the Speed of Information Processing in Human Prefrontal Cortex

Abstract: Summary Our ability to multitask is severely limited: Task performance deteriorates when we attempt to undertake two or more tasks simultaneously. Remarkably, extensive training can greatly reduce such multitasking costs. While it is not known how training alters the brain to solve the multitasking problem, it likely involves the prefrontal cortex given this brain region’s purported role in limiting multitasking performance. Here we show that the reduction of multitasking interference with training is not achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
265
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(288 citation statements)
references
References 68 publications
21
265
1
1
Order By: Relevance
“…Interestingly, the IFJ has also been referred to as a neural basis of a central, amodal bottleneck in information processing by Dux and colleagues (Dux et al, 2006(Dux et al, , 2009; see also Tombu et al, 2011). We suggest that this description is compatible with the more functional description provided by Derrfuss et al (2004) in terms of task set configuration if one assumes that the central bottleneck arises from the inability of the IFJ to update two task set configurations at once.…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 53%
“…Interestingly, the IFJ has also been referred to as a neural basis of a central, amodal bottleneck in information processing by Dux and colleagues (Dux et al, 2006(Dux et al, , 2009; see also Tombu et al, 2011). We suggest that this description is compatible with the more functional description provided by Derrfuss et al (2004) in terms of task set configuration if one assumes that the central bottleneck arises from the inability of the IFJ to update two task set configurations at once.…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 53%
“…There were only two regions showing a moderate overlap for feature and dimension costs (left SPL and right IPL), indicating that the associated processes are largely driven by different underlying neural substrates. Specifically, target dimension changes led to higher activation in pre-motor and other frontal areas, regions that have previously associated with response-selection processes (Dux et al, 2006(Dux et al, , 2009Marois, Chun & Shima, 2005), and feature changes led to higher activation in occipital areas, previously implicated in featural attention processing (e.g., Serences et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In line with this interpretation, Wager and colleagues (2005) showed that a go/no-go task, which required withholding of incorrect responses, led to significant increases in the brain areas that closely matched those activated by target dimension changes; viz. the DLPFC, right anterior PFC, premotor cortex, SMA (as well as posterior and inferior parietal regions; compare Pollmann and colleagues, 2000; see also Dux et al, 2006Dux et al, , 2009Filmer et al, 2013a,b;Tombu et al, 2011).…”
Section: Theoretical Implicationsmentioning
confidence: 95%
“…In this section we address these issues based on recent brain imaging studies and the application of videogame playing training regimens. Dux et al (2009) showed that training in a dual task reduced the activation in an area of the prefrontal cortex, namely the inferior frontal junction. The observation is consistent with the hypothesis that efficient multitasking results from a decreased reliance on brain regions involved in executive control.…”
mentioning
confidence: 99%
“…Bherer et al (2005) showed that training improved dual-task performance in both older and younger adults. The improvement also generalized to novel task combinations.Thus, what brain imaging has revealed so far is that the emergence of efficient multitasking does not necessitate the recruitment of new brain regions (Dux et al, 2009); rather, it may be associated with better synchronization or coordination between task-related areas and more efficient use of neural resources. …”
mentioning
confidence: 99%